Education tools for entrepreneurship - Álvarez Rodríguez, Ricardo David; Wise Lozano, Jorge Alberto (Springer, 2015)
For the last decade entrepreneurship education has grown to become a major discipline in several universities and colleges, particularly in the United States, Europe, and other developed nations. Nevertheless, comprehensive entrepreneurship programs are starting to be implemented in higher-education institutions across emergent economies as well. Everywhere around the world, entrepreneurship students need to gain skills and knowledge that can help them get started and have better opportunities to succeed with their ventures. At CETYS Universidad, a private non-for-profit school in Mexico, an Entrepreneurship Concentration MBA program was designed and developed around the Entrepreneurial Life Cycle and Entrepreneurship Process frameworks. The program is intended to build entrepreneurship competencies in MBA students, nurture an innovative mindset, and help them increase their entrepreneurial self-confidence and capabilities. It is the first program of its kind to be offered in the northwest region of the country, and one of the few in Mexico. RESUMEN Durante la última década, la educación empresarial ha crecido hasta convertirse en una disciplina importante en varias universidades y colegios, particularmente en los Estados Unidos, Europa y otras naciones desarrolladas. Sin embargo, los programas integrales de emprendimiento también están comenzando a implementarse en instituciones de educación superior en economías emergentes. En todo el mundo, los estudiantes de emprendimiento necesitan adquirir habilidades y conocimientos que puedan ayudarlos a comenzar y tener mejores oportunidades para tener éxito con sus empresas. En CETYS Universidad, una escuela privada sin fines de lucro en México, se diseñó y desarrolló un programa de MBA de Concentración en Emprendimiento en torno a los marcos de Ciclo de Vida Emprendedor y Proceso de Emprendimiento. El programa está destinado a desarrollar competencias empresariales en los estudiantes de MBA, fomentar una mentalidad innovadora y ayudarlos a aumentar su confianza en sí mismos y sus capacidades empresariales. Es el primer programa de este tipo que se ofrece en la región noroeste del país y uno de los pocos en México.
Innovation in entrepreneurship education: developing competitive advantages for MBA students
Keywords: Business planning; Entrepreneurial intention; Entrepreneurship process; Entrepreneurship education; Venture capital investor; Sistema